Leadership and Justice in Islamic Perspective: Their Relevance to Contemporary Islamic Family Law - Abdul Kholik; Abdul Rahman Ismail (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2025)
Leadership and justice are two fundamental concepts in Islamic teachings that are intrinsically interconnected and serve as essential foundations for the development of a just and well-ordered social and family system. In Islamic perspective, leadership is not merely understood as an exercise of authority or power, but as a moral and legal trust (amānah) that entails responsibility for upholding truth, public welfare (maṣlaḥah), and justice. Justice (‘adl) constitutes the normative core of leadership, as the absence of justice undermines the moral and spiritual legitimacy of leadership itself. This article aims to examine the concept of leadership and justice in Islamic perspective and to analyze their relevance to contemporary Islamic family law. Employing a qualitative literature-based approach through an analysis of Qur’anic verses and Prophetic traditions, this study finds that ideal leadership—particularly within the context of family governance and legal institutions—must be grounded in the principles of trustworthiness, justice, consultation (shūrā), and piety. The Qur’an emphasizes the obligation to uphold justice in all legal and social relations, including family matters, as articulated in QS. An-Nisā’ [4]: 58 and QS. An-Nahl [16]: 90. Furthermore, the Prophet Muhammad ﷺ affirmed that just leaders attain a noble status before God. Accordingly, justice-oriented leadership plays a crucial role in ensuring the protection of rights, family harmony, and the development of a responsive and equitable system of contemporary Islamic family law. This study affirms that, in Islamic thought, justice represents both the essence and ultimate objective of leadership, while leadership functions as an instrumental mechanism for realizing justice within family and social life.